TRACES STUDY PROSPEK ALUMNI JURUSAN MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS MUHAMMADIYAH MAGELANG - Kurnia, Marlina (Universitas Muhammadiyah Magelang, 2008)
Goal of this research for graduation of the Departement of Managements in Faculty of Economics in University of Muhammadiyah Magelang assosiated with the long waiting time to obtain employment, job status and responses to the education they bad acquired. Data of the respondents have used 96respondents alumni management departement starting in 1998 until the year 2005. Elections random sample using sampling. The results of respondents between 1 to 6 months is 35.79%. Employment status of respondents who work there are 66 good people who work full time or part time, while 30 respondents who are not working and not working and looking for work have 4 people, who are seeking work 18 people, while not working and not looking for work have 1 person. Responses to education for he work that has been expressed most relevant is that as many as 24 people. Feedback from respondents was given to the departement stated taht most of the departement improve the lecturer quality 71 respondents, respondents suggestions for management students Departement says most of the foreign language have the 54 respondents.